2020
DOI: 10.1002/pd.5783
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of pregnancy outcomes between twin pregnancies with and without second‐trimester amniocentesis

Abstract: Objective To assess the amniocentesis‐related pregnancy loss rate and preterm birth rate among twin pregnancies undergoing amniocentesis. Methods A retrospective cohort study was conducted at a tertiary center. The study group included twin pregnancies undergoing amniocentesis during 16 to 22 weeks of gestation. The control group was those not undergoing amniocentesis. All amniocenteses were performed by the MFM specialists. The main outcomes were the rate of pregnancy loss (before 24 weeks) and preterm birth.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 19 publications
1
8
0
1
Order By: Relevance
“…Only abnormal ultrasound findings were associated with increased risk, similar to that reported by Cahill et al (2009). Likewise, some other studies also reported that advanced maternal age, parity, conception mode and chorionicity did not influence pregnancy loss after amniocentesis (Cahill et al, 2009;Chen et al, 2020;Daskalakis et al, 2009;Dechnunthapiphat et al, 2020;Lenis-Cordoba et al, 2013). To the authors' knowledge, there are no earlier reports on cervical length as a risk factor in twin pregnancies after amniocentesis.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Only abnormal ultrasound findings were associated with increased risk, similar to that reported by Cahill et al (2009). Likewise, some other studies also reported that advanced maternal age, parity, conception mode and chorionicity did not influence pregnancy loss after amniocentesis (Cahill et al, 2009;Chen et al, 2020;Daskalakis et al, 2009;Dechnunthapiphat et al, 2020;Lenis-Cordoba et al, 2013). To the authors' knowledge, there are no earlier reports on cervical length as a risk factor in twin pregnancies after amniocentesis.…”
Section: Discussionsupporting
confidence: 80%
“…In the recent meta-analysis, the pooled rates of fetal loss in twin pregnancies after amniocentesis within 4 weeks and before 24 weeks' gestation were 45/1932 (2.1%, 95% CI [1.5, 2.9]) and 59/2439 (2.1%, 95% CI [1.4, 2.9]), respectively (Di Mascio et al, 2020). A more recent study of twin pregnancies not in the meta-analysis included 332 twin pregnancies undergoing amniocentesis, and the pregnancy loss rate before 24 weeks was 3.0% (Dechnunthapiphat et al, 2020). Chen et al (2020) reported that the pregnancy loss rate before 28 weeks in 418 twin pregnancies was 1.91%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the most recent systematic review of procedure‐related loss in twin pregnancies, two further observational datasets have been published 5,15 . Dechnunthapiphat et al.…”
Section: Discussionmentioning
confidence: 99%